The Effects of Incentivizing Early Prenatal Care on Infant Health - Kamila Cygan-Rehm; Krzysztof Karbownik (Institute of Labor Economics (IZA), 2020)
We investigated the effects of the timing of early prenatal care on infant health by exploiting a reform that required expectant mothers to initiate prenatal care during the first ten weeks of gestation to obtain a one-time monetary transfer paid after childbirth. Applying a difference-in-differences design to individual-level data on the population of births and fetal deaths, we identified small but statistically significant positive effects of the policy on neonatal health. We further provide suggestive evidence that improved maternal health-related knowledge and behaviors during pregnancy are plausible channels through which the reform might have affected fetal health.
Keywords: I12; I18; J13; 330; prenatal care; neonatal health; conditional cash transfers; prenatal care timing